(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Cervical cancer is the leading cause of cancer related death, especially in developing countries. The aim of this study was to compare well-fixed smear and air-dried smear. MATERIALS AND METHODS: A prospective study was conducted in Kasturba Medical College, Manipal, India, from paired cervical smears made from 200 women, who attended OPD of Obstetrics and Gynecology during a period of 3 months from November 2010 to January 2011. Routine smears were fixed immediately in 95% of ethanol and stained by Pap stain. Air-dried smears were rehydrated by immersing the slides in normal saline for 30 seconds, fixed in 95% of ethanol and stained by Pap stain. All slides were examined and assessed for various cytological parameters by the pathologist. Bethesda system was followed for reporting the cytology smears. RESULTS: Among the 200 paired smears 199 were negative for epithelial lesion or malignancy. One case (0.5%) had epithelial abnormality in both wet-fixed (WF) and air-dried (AD) smears. However the AD smears showed more number of abnormal cells and cells were of higher grade than the WF smear. Detection rate of Candida was similar (12.5%) in both AD and WF smears. Identification of Trichomonas was also similar (1.5%) in both types of smears. Candida could be more easily identified in AD smears as compared to WF probably because AD had a clearer background. CONCLUSIONS: In air-dried smears, individual cells are clearly seen. The cellular and nuclear size is comparable to tissue sections.